ChemInform Abstract: Catalytic Promiscuity of Transaminases: Preparation of Enantioenriched β‐Fluoroamines by Formal Tandem Hydrodefluorination/Deamination. Issue 27 (16th June 2016) - Cuetos, Anibal; Garcia‐Ramos, Marina; Fischereder, Eva‐Maria; Diaz‐Rodriguez, Alba; Grogan, Gideon; Gotor, Vicente; Kroutil, Wolfgang; Lavandera, Ivan
Abstract: A series of racemic β‐fluoroamines is kinetically resolved by a tandem hydrodefluorination/deamination process.